2022
DOI: 10.3310/cwib0236
|View full text |Cite
|
Sign up to set email alerts
|

A multidomain decision support tool to prevent falls in older people: the FinCH cluster RCT

Abstract: Background Falls in care home residents are common, unpleasant, costly and difficult to prevent. Objectives The objectives were to evaluate the clinical effectiveness and cost-effectiveness of the Guide to Action for falls prevention in Care Homes (GtACH) programme. Design A multicentre, cluster, parallel, 1 : 1 randomised controlled trial with embedded proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…The effectiveness of the multifaceted approach is based on one recent RCT [ 206 ]. The focus of implementation interventions should be on modifiable barriers and facilitators such as communication, knowledge and skills.…”
Section: Falls In Care Homesmentioning
confidence: 99%
“…The effectiveness of the multifaceted approach is based on one recent RCT [ 206 ]. The focus of implementation interventions should be on modifiable barriers and facilitators such as communication, knowledge and skills.…”
Section: Falls In Care Homesmentioning
confidence: 99%
“…The positive findings of the FinCH trial may enhance the coherence of GtACH by removing uncertainty about its effectiveness ( 3 , 4 ). This, alongside recommendation by regulatory bodies (such as NICE and the CQC in the UK), is likely to increase participation .…”
Section: Discussionmentioning
confidence: 99%
“…The GtACH programme also demarcates two distinct staff roles: a Falls Champion located within each care home to support local practice and a regional Falls Lead offering expert support in falls risk management (Appendix 1 available online provides more detail about GtACH). The Falls in Care Homes (FinCH) randomised controlled trial has demonstrated that the GtACH programme both reduces the number of resident falls and is cost-effective ( 3 , 4 ). The findings of FinCH support the broad implementation of the GtACH programme, whilst recognising that ‘the intervention and its implementation would almost certainly require adaptation to take account of the different ways that long-term care facilities are configured’ ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies centralised PPI stakeholders within the study design which strengthened the quality and relevance of the research methodology (24,31,33). Another study utilised PPI stakeholders' recommendations to involve care home managers in recruitment which ultimately led to a 3% increase in participant recruitment per home (39).…”
Section: Experts By Experiencementioning
confidence: 99%